Estado actual del conocimiento del orden Odonata en la Patagonia - Muzón, Javier (2009)
The Odonata order is represented in Patagonia by 36 species belonging to nine families and 18 genera. The endemicity level is high being approximately 60% of the species and 40% of genera endemic. The specific richness in Patagonia decreases from West to East and from North to South, being Nahuel Buta (Chile) and Andes mountains between 38° and 41° S on the forest area, and the Somuncurá plateau (Argentina) on the steppe the richest areas. An update of its records and an analysis of the main distribution patterns are provided in this paper.